MP16: Quality of work life among nurses and physicians in Québec rural emergency departments. (15th May 2017) - Fleet, R.; Dupuis, G.; Mbakop-Nguebou, M.; Archambault, P.M.; Plant, J.; Chauny, J.; Levesque, J.; Ouimet, M.; Poitras, J.; Haggerty, J.; Légaré, F.
Abstract : Introduction: Recruitment and retention of healthcare staff are difficult in rural communities. Poor quality of work life (QWL) may be an underling factor as rural healthcare professionals are often isolated and work with limited resources. However, QWL data on rural emergency (ED) staff is limited. We assessed QWL among nurses and physicians as part of an ongoing study on ED care in Québec.Methods: We selected EDs offering 24/7 medical coverage, with hospitalization beds, in rural or small towns (Stats Canada definition). Of Québec's 26 rural EDs, 23 (88%) agreed to participate. The online Quality of Work Life Systemic Inventory (QWLSI, with 1 item per 34 "life domains"), was sent to all non-locum ED nurses and physicians (about 500 potential participants). The QWLSI is used for comparing QWL scores to those of a large international database. We present overall and subscale QWL scores as percentiles (PCTL) of scores in the large database, and comparisons of nurses' and physicians' scores (t test).Results: Thirty-three physicians and 84 nurses participated. Mean age was 39.8 years (SD=10.1): physicians=37 (7.7) and nurses=40.9 (10.7). Overall QWL scores for all were in the 32nd PCTL, i.e. low. Nurses were in the 28th PCTL and physicians in the 44nd (p>0.05). For both groups, QWL was below the 25th PCTL i.e. very low, for "sharing workload during absence of an employee", "working equipment", "flexibility of work schedule", "impact of working hours on health", "possibility of being absent for familial reasons", "relations with employees". The groups differed (p<0.05) on only two subscales: remuneration and career path. For remuneration, scores were similar on fringe benefits (nurses 22nd PCTL, physicians 32nd) and income security (nurses 72nd, physicians 74th), but differed on income level (nurses 74th, physicians 93rd). The groups differed on all 3 career path items: advancement possibilities (nurses 53th, physicians 91st), possibilities for transfer (nurses 51nd, physicians 84th) and continuing education (nurses 18th, physicians 49th).Conclusion: Overall QWL among rural ED staff is poor. Groups had similar QWL scores except on career path, with physicians perceiving better long-term prospects. Given difficulties in rural recruitment and retention, these findings suggest that QWL should be assessed in rural and urban EDs nationwide.